Crystallizer casting powder for low-carbon steel and preparation method of crystallizer casting powder
By using pre-melting materials such as SiO2 and CaO, wollastonite, ice crystals, modified carbon black and modified dextrin in the crystallizer for low carbon steel, the problems of carbon increase and poor thermal stability of the adhesive are solved, the appropriate melting speed and viscosity of the protective slag are achieved, and its insulation performance and service life are improved.
Patent Information
- Application Number
- CN202411625739.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-25
AI Technical Summary
The existing low-carbon steel crystallizer protective slag is prone to carbon increase problems in continuous casting production, and the commonly used adhesives have poor thermal stability, which affects the service life of the protective slag.
SiO2, CaO, etc. are used as the main components of the pre-melting material, and add wollastonite, ice crystallizer, modified carbon black and modified dextrin to synthesize low-carbon steel crystallizer to protect the slag. Through the coating of composite powder and the modification of adhesive, the melting speed and viscosity of the protective slag are improved.
The protective slag for low carbon steel crystallizer has an appropriate melting speed and viscosity, and improves the insulation performance and service life of the protective slag, which is suitable for low carbon steel field.
Smart Images

Figure BDA0005134688620000081 
Figure BDA0005134688620000091
Abstract
Description
Technical Field
[0001] The invention relates to the field of mold protection slag, and in particular to a mold protection slag for low-carbon steel and a preparation method thereof. Background Art
[0002] Mold protection slag is a material placed on the surface of the molten steel in the mold during continuous steel casting to keep warm, prevent oxidation and absorb non-metallic inclusions. It has become an important part of modern continuous casting technology. The efficiency of continuous casting and the development of different types of steel are closely related to it. It is a key technology to control the surface quality of the ingot and the smooth pouring process during continuous casting.
[0003] Low carbon steel has the advantages of good high temperature mechanical properties, no serious phase change and volume change during solidification, low internal stress and crack sensitivity, etc. Based on the solidification characteristics and quality requirements of low carbon steel itself, the lubrication and consumption of the protective slag are mainly considered during design. Therefore, the crystallizer protective slag of low carbon steel is required to have a suitable melting rate and viscosity.
[0004] However, the most common problem in the current continuous casting production of low-carbon steel is carbon addition, which requires scientific researchers to introduce as little carbonaceous materials as possible or not use carbonaceous materials. However, if carbonaceous materials are not used, the thermal insulation effect of the crystallizer protective slag will be poor, which has become a major difficulty in current production. In addition, dextrin and corn starch adhesives are often used in the preparation of crystallizer protective slag, but such adhesives are bio-based substances and may have problems with poor thermal stability.
[0005] Patent CN 103121089B discloses a colored continuous casting crystallizer protection slag for ultra-low carbon steel. The crystallizer protection slag provided in the application includes fluorite powder, industrial soda ash, wollastonite powder, lithium carbonate, red iron oxide, adhesive and water reducer and other ingredients, and does not add any carbonaceous materials, thereby solving the problem of carbon increase in the existing crystallizer protection slag. However, the application does not disclose the specific type of adhesive used. From the perspective of the prior art, most of the adhesives currently used have the problem of poor thermal stability, which may reduce the service life of the crystallizer protection slag.
[0006] Therefore, there is an urgent need on the market for a mold protection slag for low carbon steel with suitable melting speed and viscosity. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention uses SiO2, CaO and the like as the main components of the premelt, adds wollastonite, cryolite, modified carbon black and adhesive and the like to synthesize a crystallizer protective slag for low carbon steel, which has a suitable melting rate and viscosity.
[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] On the one hand, the present invention provides a crystallizer protective slag for low carbon steel. The crystallizer protective slag for low carbon steel comprises the following raw materials, measured by weight: 50-60 parts of premelt, 5-10 parts of wollastonite, 5-10 parts of cryolite, 10-15 parts of fluorite, 2-4 parts of bauxite, 1-3 parts of glass powder, 1-3 parts of modified carbon black, 2-5 parts of graphite, and 2-6 parts of adhesive.
[0010] In some embodiments of the present invention, the premelt comprises the following raw materials in weight percentage: SiO2 40-50%, CaO 35-45%, Al2O3 2-5%, Na2O 3-6%, MgO 3-6%, F - 5-9%.
[0011] In some embodiments of the present invention, the method for preparing the modified carbon black comprises the following steps:
[0012] (1) titanium dioxide, cerium trioxide and carbon black are mixed, anhydrous ethanol is added, ball milled, and dried to obtain a composite powder for later use;
[0013] (2) adding the composite powder of step (1) into a reaction container, adding PVP and deionized water, ultrasonicating, stirring, and obtaining a dispersion for use;
[0014] (3) mixing TEOS, deionized water and anhydrous ethanol, adding dilute hydrochloric acid aqueous solution, heating and stirring to obtain silica sol for use;
[0015] (4) adding zirconium oxychloride octahydrate into deionized water, stirring, adding ammonia water, stirring, and obtaining zirconium sol for use;
[0016] (5) The silica sol of step (3) and the zirconium sol of step (4) are simultaneously added dropwise to the dispersion of step (2), the pH is adjusted to 4-5, stirred, centrifuged, dried, a mineralizer is added, and calcined under an inert atmosphere to obtain modified carbon black.
[0017] Wherein, the mineralizer in step (5) is LiF.
[0018] In some embodiments of the present invention, in step (1), the mass ratio of carbon black, titanium dioxide and cerium oxide is 1:(0.3-0.7):(0.5-1).
[0019] Preferably, in step (1), the mass ratio of carbon black, titanium dioxide and cerium oxide is 1:0.5:0.67.
[0020] In some embodiments of the present invention, the mass ratio of the composite powder, TEOS and zirconium oxychloride octahydrate is 1:(8.5-9):(13-14).
[0021] Preferably, the mass ratio of the composite powder, TEOS and zirconium oxychloride octahydrate is 1:8.75:13.5.
[0022] The thermal insulation performance of the mold protection slag is very important, which plays an important role in the smooth continuous casting of low carbon steel. Carbon black has good thermal insulation performance and can effectively control the melting rate to ensure the supply of liquid slag. Increasing the carbon black content can effectively enhance the thermal insulation performance of the mold protection slag. However, too high carbon black will cause carbon increase in low carbon steel. Therefore, improving the thermal insulation performance of carbon black becomes increasingly important.
[0023] On the one hand, the applicant mixed titanium dioxide, cerium trioxide and carbon black to prepare a composite powder. Titanium dioxide has the characteristics of corrosion resistance and high hardness. The rare earth metal cerium in cerium trioxide can make the viscosity of the crystallizer protective slag suitable, and it also has good thermal insulation properties. Mixing the two with carbon black is beneficial to improving the comprehensive performance of the crystallizer protective slag; on the other hand, the applicant prepared silica sol and zirconium sol, and selected LiF as a mineralizer. The composite powder was uniformly densified by using silica sol and zirconium sol at the same time, which can effectively improve the high-temperature stability of the composite powder, thereby improving the thermal insulation properties of carbon black, and making the crystallizer protective slag have a suitable melting rate and viscosity.
[0024] In some embodiments of the present invention, the method for preparing the adhesive comprises the following steps:
[0025] 1) corn dextrin, trimethylol melamine resin, borax and deionized water are mixed, stirred at 85-95° C. for 20-40 min, sodium hydroxide aqueous solution is added, sealed and cooled, and modified dextrin is obtained for later use;
[0026] 2) Mix PEG400 and acetone, add toluene diisocyanate, heat, stir, and keep warm to obtain a solution for later use;
[0027] 3) adding the modified dextrin in step 1) into deionized water, heating, adding the solution in step 2), heating, stirring, cooling, adding di-n-butylamine, stirring, and rotary evaporation to obtain an adhesive.
[0028] In some embodiments of the present invention, the mass ratio of corn dextrin, trimethylol melamine resin and toluene diisocyanate is 1:(0.2-0.4):(0.2-0.4).
[0029] Preferably, the mass ratio of corn dextrin, trimethylol melamine resin and toluene diisocyanate is 1:0.33:0.33.
[0030] Mold powder plays a vital role in continuous casting production. The performance of the binder has a direct impact on the overall effect of the mold powder, such as the stability, strength and viscosity of the mold powder, which in turn affects the melting performance, lubrication performance and crystallization performance of the mold powder. Among them, the commonly used binder for mold powder is dextrin, which is green and environmentally friendly and has good adhesion. However, as a biomass material, dextrin may be insufficiently stable when exposed to high temperature for a long time.
[0031] The applicant uses corn dextrin, trimethylol melamine resin and borax as raw materials, and controls the ratio of corn dextrin to trimethylol melamine resin to cross-link some hydroxyl groups in corn dextrin and trimethylol melamine resin, thereby preparing a modified dextrin with good fluidity and a network molecular structure, thereby improving the stability of the dextrin and also improving the adhesion of the dextrin to a certain extent; further, the applicant introduces toluene diisocyanate to modify the modified dextrin, thereby improving the adhesion and stability of the modified dextrin, and the toluene diisocyanate resin may cross-link with the hydroxyl and hydroxymethyl groups in the modified dextrin to a certain extent, thereby improving the stability of the adhesive.
[0032] Another aspect of the present invention further provides a method for preparing the mold slag for low carbon steel described in the above technical solution, comprising the following steps:
[0033] Premelt, wollastonite, cryolite, fluorite, bauxite and glass powder are mixed, melted, water quenched, dried, crushed, modified carbon black, graphite and adhesive are added, stirred, ball milled, slurried and spray granulated to obtain mold protective slag for low carbon steel.
[0034] In some embodiments of the present invention, the pulverizing operation is pulverizing to 200-300 meshes.
[0035] In some embodiments of the present invention, the low carbon steel mold protection slag obtained by the preparation method has a melting rate of 25-40s and a viscosity of 0.25-0.45 Pa·s at 1300°C.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The present invention uses SiO2, CaO and the like as the main components of the premelt, and adds wollastonite, cryolite, modified carbon black and adhesive to synthesize a crystallizer protective slag for low carbon steel. Through the synergistic effect of the various components, the crystallizer protective slag for low carbon steel has the advantages of suitable melting speed and viscosity.
[0038] (2) The present invention mixes titanium dioxide, cerium trioxide and carbon black to prepare a composite powder, and prepares silica sol and zirconium sol to uniformly densify the composite powder at the same time, which can effectively improve the high-temperature stability of the composite powder, thereby improving the thermal insulation performance of carbon black, and thus making the crystallizer protective slag have a suitable melting rate and viscosity.
[0039] (3) The present invention uses corn dextrin, trimethylol melamine resin and borax as raw materials to prepare modified dextrin, and then introduces toluene diisocyanate to modify the modified dextrin, thereby improving the adhesion and stability of the modified dextrin, which is beneficial for the crystallizer protective slag to have a suitable melting rate and viscosity.
[0040] (4) The mold protection slag prepared by the present invention has a suitable melting rate and viscosity, can be widely used in the field of low-carbon steel, and has good commercial application value. DETAILED DESCRIPTION
[0041] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0042] In the following examples and comparative examples, except for the modified carbon black and the adhesive, the other compound monomers and related reagents used can be purchased from the market, among which PVP was purchased from Wuhan Smack Biotechnology Co., Ltd.; trimethylol melamine resin was purchased from Hubei Wonder Chemical Co., Ltd.; PEG400 was purchased from Hai'an Petrochemical Plant in Jiangsu Province.
[0043] Preparation Example 1
[0044] The synthesis method of modified carbon black A comprises the following steps:
[0045] (1) 15 g of titanium dioxide, 20 g of cerium trioxide and 30 g of carbon black were mixed, 200 ml of anhydrous ethanol was added, ball milled for 30 min, and dried at 110 ° C for 4 h to obtain a composite powder for use;
[0046] (2) Add 2 g of the composite powder of step (1) into a reaction container, add 2 g of PVP and 80 ml of deionized water, sonicate for 10 min, stir for 24 h, and obtain a dispersion for use;
[0047] (3) 17.5 g of TEOS, 12 ml of deionized water and 35 g of anhydrous ethanol were mixed, 1 wt % of dilute hydrochloric acid aqueous solution was added to adjust the pH to 3, the mixture was heated to 60° C. and stirred for 45 min to obtain a silica sol for use;
[0048] (4) adding 27 g of zirconium oxychloride octahydrate to 136 ml of deionized water, stirring for 20 min, adding 2.5 wt % ammonia water to adjust the pH to 3, stirring for 30 min, and obtaining a zirconium sol for use;
[0049] (5) The silica sol of step (3) and the zirconium sol of step (4) are simultaneously added dropwise to the dispersion of step (2), the pH is adjusted to 4.5, stirred for 5 hours, centrifuged, dried at 110° C. for 4 hours, 6 g of LiF is added, and calcined at 1100° C. for 30 minutes under an argon atmosphere to obtain modified carbon black A.
[0050] Preparation Example 2
[0051] The specific implementation method of modified carbon black B is the same as that of modified carbon black A, except that in step (1), the mass of titanium dioxide is replaced by 8 g.
[0052] Preparation Example 3
[0053] The specific implementation method of modified carbon black C is the same as that of modified carbon black A, except that in step (1), the mass of cerium trioxide is replaced by 14.5 g.
[0054] Preparation Example 4
[0055] The specific implementation method of modified carbon black D is the same as that of modified carbon black A, except that in step (3), the mass of TEOS is replaced by 16.5 g.
[0056] Preparation Example 5
[0057] The specific implementation method of modified carbon black E is the same as that of modified carbon black A, except that in step (4), the mass of zirconium oxychloride octahydrate is replaced with 25 g.
[0058] Preparation Example 6
[0059] The synthesis method of adhesive A comprises the following steps:
[0060] 1) 60 g corn dextrin, 20 g trimethylol melamine resin, 1.2 g borax and 100 ml deionized water were mixed, stirred at 90° C. for 30 min, 0.01 mol / L sodium hydroxide aqueous solution was added to adjust the pH to 9.5, and the mixture was sealed and cooled to room temperature to obtain modified dextrin for later use;
[0061] 2) Mix 40 g of PEG400 and 100 ml of acetone, add 20 g of toluene diisocyanate, heat to 80°C, stir for 3 h, and keep warm to 50°C to obtain a solution for use;
[0062] 3) Add the modified dextrin of step 1) into 300 ml of deionized water, heat to 60° C., add the solution of step 2), heat to 120° C., stir for 4 h, cool to 70° C., add 5 g of di-n-butylamine, stir for 30 min, and rotary evaporate to obtain adhesive A.
[0063] Preparation Example 7
[0064] Adhesive B has the same specific implementation as Adhesive A, except that in step 1), the mass of trimethylolmelamine resin is replaced with 11 g.
[0065] Preparation Example 8
[0066] Adhesive C, the specific implementation manner is the same as Adhesive A, except that: in step 2), the mass of toluene diisocyanate is replaced with 11 g.
[0067] Example 1
[0068] A mold protection slag for low carbon steel comprises the following raw materials by weight: 55 parts of premelt, 7.5 parts of wollastonite, 7.5 parts of cryolite, 12.5 parts of fluorite, 3 parts of bauxite, 2 parts of glass powder, 2 parts of modified carbon black A, 3.5 parts of graphite and 4 parts of adhesive A.
[0069] The premelt is made of the following raw materials in weight percentage: SiO2 44%, CaO 39%, Al2O33%, Na2O4%, MgO 4%, F - 6%.
[0070] The method for preparing mold slag for low carbon steel in this embodiment comprises the following steps:
[0071] The premelt, wollastonite, cryolite, fluorite, bauxite and glass powder are mixed, melted at 1200°C, quenched in water, dried at 105°C for 12 hours, crushed to 250 mesh, modified carbon black A, graphite and binder A are added, stirred for 2 hours, ball milled for 30 minutes, slurried, spray granulated, and thus the mold protective slag for low carbon steel is obtained.
[0072] Example 2
[0073] A low-carbon steel mold protection slag comprises the following raw materials by weight: 50 parts of premelt, 5 parts of wollastonite, 5 parts of cryolite, 10 parts of fluorite, 2 parts of bauxite, 1 part of glass powder, 2 parts of modified carbon black A, 2 parts of graphite and 2 parts of adhesive A.
[0074] The premelt is made of the following raw materials in weight percentage: SiO2 40%, CaO 45%, Al2O32%, Na2O5%, MgO 3%, F - 5%.
[0075] The method for preparing mold slag for low carbon steel in this embodiment comprises the following steps:
[0076] The premelt, wollastonite, cryolite, fluorite, bauxite and glass powder are mixed, melted at 1200°C, quenched in water, dried at 105°C for 12 hours, crushed to 200 mesh, modified carbon black A, graphite and binder A are added, stirred for 2 hours, ball milled for 30 minutes, slurried, spray granulated, and thus the mold protective slag for low carbon steel is obtained.
[0077] Example 3
[0078] A low-carbon steel mold protection slag comprises the following raw materials by weight: 60 parts of premelt, 10 parts of wollastonite, 10 parts of cryolite, 15 parts of fluorite, 4 parts of bauxite, 3 parts of glass powder, 2 parts of modified carbon black A, 5 parts of graphite and 6 parts of adhesive A.
[0079] The premelt is made of the following raw materials in weight percentage: SiO2 48%, CaO 35%, Al2O32%, Na2O3%, MgO 3%, F - 9%.
[0080] The method for preparing mold slag for low carbon steel in this embodiment comprises the following steps:
[0081] The premelt, wollastonite, cryolite, fluorite, bauxite and glass powder are mixed, melted at 1200°C, quenched in water, dried at 105°C for 12 hours, crushed to 300 mesh, modified carbon black A, graphite and binder A are added, stirred for 2 hours, ball milled for 30 minutes, slurried, spray granulated, and thus the crystallizer protective slag for low carbon steel is obtained.
[0082] Example 4
[0083] A low-carbon steel mold protection slag comprises the following raw materials by weight: 52 parts of premelt, 6 parts of wollastonite, 6 parts of cryolite, 11 parts of fluorite, 2.5 parts of bauxite, 1.5 parts of glass powder, 1 part of modified carbon black A, 3 parts of graphite and 4 parts of adhesive A.
[0084] The premelt is the same as in Example 1.
[0085] The preparation method of the mold protection slag for low carbon steel in this embodiment is the same as that in Example 1.
[0086] Example 5
[0087] A low-carbon steel mold protection slag comprises the following raw materials by weight: 58 parts of premelt, 9 parts of wollastonite, 9 parts of cryolite, 14 parts of fluorite, 3 parts of bauxite, 2.5 parts of glass powder, 3 parts of modified carbon black A, 4 parts of graphite and 4 parts of adhesive A.
[0088] The premelt is the same as in Example 1.
[0089] The preparation method of the mold protection slag for low carbon steel in this embodiment is the same as that in Example 1.
[0090] Example 6
[0091] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified carbon black A is replaced by modified carbon black B in equal amounts.
[0092] Example 7
[0093] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified carbon black A is replaced by modified carbon black C in equal amounts.
[0094] Example 8
[0095] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified carbon black D replaces modified carbon black A in equal amounts.
[0096] Example 9
[0097] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that modified carbon black E replaces modified carbon black A in equal amounts.
[0098] Example 10
[0099] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the adhesive A is replaced by an equal amount of adhesive B.
[0100] Embodiment 11
[0101] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that the adhesive A is replaced by an equal amount of adhesive C.
[0102] Example 12
[0103] This embodiment provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that corn dextrin is used to replace the binder A in an equal amount.
[0104] Comparative Example 1
[0105] This comparative example provides a mold protection slag for low carbon steel and a preparation method thereof. The specific implementation method is the same as that of Example 1, except that an equal amount of carbon black is used to replace modified carbon black A.
[0106] Performance Testing
[0107] The melting speed and viscosity of the low carbon steel mold protection slag of the above Examples 1-12 and Comparative Example 1 were tested. The test results are shown in Table 1.
[0108] The melting rate is tested by the melt dripping test, that is, the sample is heated until it melts, and the time for the melt to drip is recorded;
[0109] Viscosity reference standard YB / T185-2017.
[0110] Table 1
[0111]
[0112]
[0113] It can be seen from the data in Table 1 that the overall melting rate of the mold protection slag for low carbon steel in Examples 1-5 of the present invention is 30-40s, and the viscosity is in the range of 0.25-0.45Pa·s at 1300°C, that is, it has a suitable melting rate and viscosity. Among them, Examples 6-9 changed the addition ratio of the main components in the synthesis process of modified carbon black, so that the thermal insulation of the modified carbon black was not well improved, resulting in a decrease in the melting rate and viscosity of the mold protection slag, which exceeded the appropriate range; Examples 10-11 changed the modification ratio of trimethylol melamine resin and toluene diisocyanate to corn dextrin in the adhesive, so that the thermal stability and adhesion of the adhesive were not well improved, which resulted in the melting rate and viscosity of the mold protection slag for low carbon steel exceeding the appropriate range; Example 12 and Comparative Example 1 respectively selected corn dextrin and carbon black to replace adhesive A and modified carbon black A in equal amounts, and the test found that the melting rate and viscosity of the mold protection slag for low carbon steel showed poor results.
[0114] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A mold protection slag for low carbon steel, characterized in that: The low carbon steel mold protection slag comprises the following raw materials by weight: 50-60 parts of premelt, 5-10 parts of wollastonite, 5-10 parts of cryolite, 10-15 parts of fluorite, 2-4 parts of bauxite, 1-3 parts of glass powder, 1-3 parts of modified carbon black, 2-5 parts of graphite and 2-6 parts of adhesive.
2. The mold powder for low carbon steel according to claim 1, characterized in that: The premelt comprises the following raw materials in weight percentage: SiO2 40-50%, CaO 35-45%, Al2O3 2-5%, Na2O 3-6%, MgO 3-6%, F - 5-9%.
3. The mold powder for low carbon steel according to claim 1, characterized in that: The preparation method of the modified carbon black comprises the following steps: (1) titanium dioxide, cerium trioxide and carbon black are mixed, anhydrous ethanol is added, ball milled, and dried to obtain a composite powder for later use; (2) adding the composite powder of step (1) into a reaction container, adding PVP and deionized water, ultrasonicating, stirring, and obtaining a dispersion for use; (3) Mix TEOS, deionized water and anhydrous ethanol, add dilute hydrochloric acid aqueous solution, heat and stir to obtain silica sol for use; (4) adding zirconium oxychloride octahydrate to deionized water, stirring, adding ammonia water, stirring, and obtaining zirconium sol for use; (5) The silica sol of step (3) and the zirconium sol of step (4) are simultaneously added dropwise to the dispersion of step (2), the pH is adjusted to 4-5, stirred, centrifuged, dried, a mineralizer is added, and calcined under an inert atmosphere to obtain modified carbon black.
4. The mold powder for low carbon steel according to claim 3, characterized in that: In the step (1), the mass ratio of carbon black, titanium dioxide and cerium trioxide is 1: (0.3-0.7): (0.5-1).
5. The mold powder for low carbon steel according to claim 3, characterized in that: The mass ratio of the composite powder, TEOS and zirconium oxychloride octahydrate is 1:(8.5-9):(13-14).
6. The mold powder for low carbon steel according to claim 1, characterized in that: The preparation method of the adhesive comprises the following steps: 1) Mix corn dextrin, trimethylol melamine resin, borax and deionized water, stir at 85-95°C for 20-40 minutes, add sodium hydroxide aqueous solution, seal and cool, and obtain modified dextrin for use; 2) Mix PEG 400 and acetone, add toluene diisocyanate, heat, stir, and keep warm to obtain a solution for use; 3) Add the modified dextrin in step 1) into deionized water, heat it, add the solution in step 2), heat it, stir it, cool it down, add di-n-butylamine, stir it, and rotary evaporate it to obtain an adhesive.
7. The mold powder for low carbon steel according to claim 6, characterized in that: The mass ratio of the corn dextrin, trimethylol melamine resin and toluene diisocyanate is 1:(0.2-0.4):(0.2-0.4).
8. A method for preparing mold slag for low carbon steel according to any one of claims 1 to 7, characterized in that: The following steps are involved: Premelt, wollastonite, cryolite, fluorite, bauxite and glass powder are mixed, melted, water quenched, dried, crushed, modified carbon black, graphite and adhesive are added, stirred, ball milled, slurried and spray granulated to obtain mold protective slag for low carbon steel.
9. The method for preparing mold powder for low carbon steel according to claim 7, characterized in that: The particle size of the crushed particles is 200-300 meshes.
10. The method for preparing mold powder for low carbon steel according to claim 7, characterized in that: The low-carbon steel mold protection slag obtained by the preparation method has a melting speed of 30-40s and a viscosity of 0.25-0.45 Pa·s at 1300°C.
Citation Information
Patent Citations
Colorful continuous casting crystallizer covering slag for ultra-low carbon steel
CN103121089B
Cited By
Low-alkalinity high-crystallization casting powder for pen point steel
CN121870031A